2023
DOI: 10.1001/jamanetworkopen.2023.9321
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Esketamine for Supplemental Analgesia During Elective Cesarean Delivery

Abstract: ImportanceEpidural anesthesia is a primary choice for cesarean delivery, but supplemental analgesics are often required to relieve pain during uterine traction.ObjectiveTo investigate the sedative and analgesic effects of intravenous esketamine administered before childbirth via cesarean delivery with the patient under epidural anesthesia.Design, Setting, and ParticipantsThis multicenter, double-blind randomized clinical trial assessed 903 women 18 years or older who had full-term single pregnancy and were sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 40 publications
3
14
0
Order By: Relevance
“…However, further studies are required to confirm the role of antihyperalgesics in the preventive effect of esketamine on PPD. In addition, there were no notable neurologic symptoms observed during the postoperative period in the esketamine group, in line with previous reports …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, further studies are required to confirm the role of antihyperalgesics in the preventive effect of esketamine on PPD. In addition, there were no notable neurologic symptoms observed during the postoperative period in the esketamine group, in line with previous reports …”
Section: Discussionsupporting
confidence: 92%
“…Numerous studies have found that an esketamine nasal spray could rapidly induce and sustain beneficial effects for patients with a diagnosis of treatment-resistant depression and risk of suicides . Previous studies have also found that, for women who have undergone cesarean deliveries, a preventive administration of esketamine, either by the intrathecal or intravenous route, could yield both safe and efficacious analgesic effects . Given its bidirectional efficacy as an analgesic and antidepressant, we performed a double-blind, randomized clinical trial to investigate the effects of perioperative adjunctive esketamine administration during cesarean delivery on patients with PPD.…”
Section: Introductionmentioning
confidence: 99%
“…In China, Esketamine, the enantiomer of ketamine has also been widely used in recent years. Some researchers have investigated the safety of supplemental use of Esketamine in cesarean delivery for pregnancy and neonates but focused on its short‐term effects 53,54 . It is also of great importance to compare the long‐term effects of these two enantiomers in our model in the future.…”
Section: Discussionmentioning
confidence: 99%
“…One promising alternative is esketamine, an N -methyl- d -aspartate receptor antagonist and the dextrorotatory isomer of ketamine. Esketamine possesses twice the potency of ketamine in terms of hypnotic and analgesic effects, with fewer psychiatric adverse effects . Previous studies have also indicated that a subanesthetic dose of esketamine can maintain hemodynamic stability and reduce respiratory depression in surgical patients .…”
Section: Introductionmentioning
confidence: 99%